KESTABILAN MODEL SUSCEPTIBLE VACCINATED INFECTED RECOVERED (SVIR) PADA PENYEBARAN PENYAKIT CAMPAK (MEASLES) (Studi Kasus di Kota Semarang) - Haryati, Melita; ., Kartono; ., Sunarsih (MATEMATIKA, 2014)
Measles is the disease that caused by paramixovirus that infected to the humans by direct contact with infected person. Measles in Semarang was still as endemic disease. The aim of this study is analyze the SVIR (Susceptible Vaccinated Invected Recovered) model of the spread of Measles. This model is a system of nonlinear differential equation which solved by numerical solution with Euler’s method. The study use the data from Semarang Health Department, from the SVIR model generated , disease free equlibrium . If the vaccination rate is increasing, so susceptible people will be decreased and increasing the recovered people. Based on the result of analysis SVIR model in the strategy to control the spread of Measles can be done by developing the program of Measles’ vaccination.